Effect of the arterial needle bevel position on puncture pain and postremoval bleeding time in hemodialysis patients: A self‐controlled, single‐blind study. Issue 4 (6th September 2022) - Ozen, Nurten; Tosun, Betul; Sayilan, Aylin Aydin; Eyileten, Tayfun; Ozen, Volkan; Ecder, Tevfik; Tosun, Nuran
Abstract: Aim: This study aimed to investigate the effect of the bevel orientation (facing upwards or downwards towards the skin) of the needle inserted into the arterial limb of the arteriovenous fistula (AVF) on puncture pain and postremoval bleeding time. Methods: This study, using a single‐blind crossover design, was conducted on 35 maintenance hemodialysis patients who had been dialyzed for at least 6 months and in whom blood access was via an AVF. AVF cannulation was performed with the needle bevel pointing upward in the first six sessions and the needle bevel pointing downwards (towards the skin) in the subsequent six sessions. Needles were always inserted in the direction of blood flow. At each dialysis session, cannulation pain was measured using a visual analog scale (VAS), and the bleeding time at the end of dialysis after needle removal was recorded. Findings: The VAS score and postremoval bleeding time were lower when the needle bevel pointed downwards towards the skin during insertion ( P < 0.05). Discussion: Insertion of the needle with the bevel pointed downward decreased puncture pain during cannulation and bleeding time postdialysis on needle removal.